A Case of Renal Cell Carcinoma withIpsilateral Renal Pelvic Metastasis Mimicking Double Cancer - Hikami, Kensuke (Hinyokika kiyo. Acta urologica Japonica, 2018)
A 71-year-old man with left flank pain was referred to our hospital. Computed tomography (CT) revealed a left renal tumor, left renal pelvic wall thickening, bilateral adrenal gland swelling, multiple pulmonary nodules, and a bone metastatic tumor. Further, positron emission tomography/CT revealed increased 18F fluorodeoxyglucose uptake in the left renal tumor, multiple pulmonary nodules, and bone metastatic tumor. Accordingly, we performed biopsies of the thickening of the left renal pelvic wall and bone metastatic tumor, and histological examinations revealed an unknown type carcinoma and bone metastasis from clear cell carcinoma. Without a precise preoperative diagnosis of the thickening of the left renal pelvic wall, laparoscopic left nephrectomy was performed, and the renal and renal pelvic wall tumors were diagnosed as clear cell carcinoma on pathological examination. Therefore, we made a final diagnosis of renal cell carcinoma with lung, bone, and renal pelvic metastases. Although axitinib was administered, cervical spine metastasis developed. Unfortunately, the patient died from disease progression five months following the surgery